Helical resonator filters with improved multipactor performance exploiting rigorous modelling and the large gap approach. Issue 10 (16th May 2019) - Salza, Giuseppe; Goussetis, George; Vicente, Carlos; Kosmopoulos, Savvas; Reglero, Marta; Taroncher, Máriam; Boria, Vicente E.; Sidiropoulos, Nikolas; Galdeano, Jaione
Abstract : The power handling capability of helical resonator filters is studied by means of the parallel plate model (employed in the European Cooperation for Space Standardisation) and more rigorous modelling techniques (like the one available in the commercial software tool SPARK3D™) as well as through an experimental test campaign. The results indicate that the parallel plate model provides conservative power handling capabilities for this class of filters, while rigorous modelling can better capture the impact of the geometrical features on multipactor evolution. Although the accuracy of the estimated power handling depends on the knowledge of the practical secondary emission yield values, the use of such rigorous modelling tools enables the design of helical resonator filters with improved power handling capability by exploiting the large gap approach, therefore opening opportunities to avoid additional dielectric fillings.